Monitoring and Evaluation: Civil Society Organisations’ Competitive Edge in Effective Poverty Alleviation (The Pakistan Development Review, 2003)
The role of Civil Society Organisations as preferred partners in development is strongly emerging across the globe. Among many reasons, one is reasonably good governance. The social sector has shown the acumen to learn and apply corporate management practices and international standards fast enough to start leading the competition. Notwithstanding the fact that a large part of development funding under soft loans and grants is channeled to the government, the CSOs receive a significant share directly and indirectly to implement development projects in communities. It has opened tremendous opportunities for CSOs to experiment and evolve new approaches in project management, community organisation, service delivery, product development, resource mobilisation and financial management. What makes the civil society organisations different from the public sector organisations? Fundamentally two things; these are non-governmental and nonprofit. However, the real difference is in the way civil society organisations are managed. It includes leadership, commitment, professionalism, systems and practices, thrust of work and most of all performance.